PENGEMBANGAN MODUL PEMBELAJARAN GENETIKA BERBASIS FENOMENA LOKAL - Suratsih, Victoria Henuhili, Tutiek Rahayu, dan Muhammad Luthfi Hidayat (Jurnal Cakrawala Pendidikan, 2009)
AbstractThis study aimed to find out the gene inheritance pattern of the gembel hair in afamily in Solomerto Village, Solomerto District, Wonosobo Regency, to design alocal phenomenon based module for genetics learning, and to investigate thereadability of the learning module. This study was based on the data of the familytree map of a family with the gembel hair inheritance that could be traced to threegenerations so that this fulfilled the requirements to trace the gene inheritance. Thedata on the gembel hair inheritance were collected through observations andinterviews. The data were then analyzed to find out the characteristic inheritanceby making a map of the family tree and determining the genotype possibility ofeach family member. To investigate the readability of the module, 20 students ofSMA Negeri 8 Yogyakarta were selected as the sample. The data were analyzedusing the qualitative descriptive technique. The results of the study on the basis ofthe family tree map showed that the gembel hair gene inheritance was determinedby the recessive autosomal gene. The students gave positive responses to the localphenomenon based learning module in terms of the material coverage, the materialexplanation, the number of test items, the item difficulty level, the instruction, andthe key answers.Keywords: genetics, local phenomenon, learning module, gembel hair